IMPACT OF PERSONALITY TRAITS, COPING STRATEGIES, AND SOCIAL SUPPORT IN REHABILITATION OF SEVERE BURN PATIENTS - PARVEEN, R; NISA, QU; ANEES, T; DILDAR, N (Biological and Clinical Sciences Research Journal, 2024)
Severe burn injuries pose significant physical, psychological, and social challenges for survivors, particularly in low- and middle-income countries like Pakistan. Personality traits, coping strategies, and social support are critical factors influencing rehabilitation outcomes, yet limited research has been conducted on their impact in the Pakistani context. Objective: To evaluate the role of personality traits, coping strategies, and social support in determining rehabilitation outcomes among severe burn patients in Pakistan. Methods: This descriptive cross-sectional study was conducted at the Burn Care Unit of Nishtar Hospital, Multan. Sixty severe burn patients aged 18–60 years were recruited using purposive sampling. Data were collected through structured interviews and validated tools, including the Big Five Personality Inventory, Brief COPE questionnaire, and Multidimensional Scale of Perceived Social Support. Rehabilitation outcomes were assessed using physical, psychological, and social reintegration metrics. Data were analyzed using SPSS version 26, with descriptive and inferential statistics applied. Results: Resilient personality traits, such as emotional stability and optimism, were associated with positive rehabilitation outcomes in 80% of participants, while neuroticism correlated with poorer outcomes in 75% of cases. Problem-focused coping was reported as the most effective strategy by 83.3% of participants, whereas avoidance coping was linked to poor progress in 16.7%. Social support, particularly from family members (83.3%), significantly enhanced rehabilitation outcomes. However, societal stigma and limited access to rehabilitation services were identified as key barriers to recovery. Conclusion: Personality traits, adaptive coping strategies, and social support are pivotal in improving rehabilitation outcomes for severe burn patients in Pakistan. Addressing societal stigma and expanding access to comprehensive rehabilitation services are essential for enhancing recovery and quality of life. These findings provide valuable insights for developing culturally relevant, evidence-based interventions to support burn survivors.